2018
DOI: 10.1002/brb3.1135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and quality of life in Chinese patients with multiple system atrophy

Abstract: ObjectivesMultiple system atrophy (MSA) is a progressive neurodegenerative disorder that causes early sustained disability and poor health‐related quality of life (HrQoL). The clinical features and their effects on the HrQoL of patients in China have received little attention in the research literature. We evaluated the clinical characteristics and HrQoL of Chinese patients with MSA.Materials and MethodsA total of 143 patients with MSA from the Department of Neurology, Shanghai Ruijin Hospital, were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 28 publications
5
29
1
Order By: Relevance
“…[3,4,26,27] In our study, the depressive emotion was related to the EQ-VAS score of MSA-C. We also found that anxiety played an important role in the decreasing EQ-VAS score of MSA. [3] Attempts to treat these symptoms are important to improve the HRQoL of patients with MSA. Similar to the result of the previous study, we found that female sex was a negative determinant of health utility values of MSA.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…[3,4,26,27] In our study, the depressive emotion was related to the EQ-VAS score of MSA-C. We also found that anxiety played an important role in the decreasing EQ-VAS score of MSA. [3] Attempts to treat these symptoms are important to improve the HRQoL of patients with MSA. Similar to the result of the previous study, we found that female sex was a negative determinant of health utility values of MSA.…”
Section: Discussionmentioning
confidence: 53%
“…[3][4][5]10] These studies found that the most frequently affected dimensions in MSA were mobility, self-care, and usual activities. [3][4][5]10] Besides the severity of the disease [4][5][6]11], some studies found that depression was the determinant of HRQoL of MSA. [3,5] No study on QoL of MSA evaluated by using EQ-5D-5L was available.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations